2022
DOI: 10.3389/fimmu.2022.724139
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines in progression, chemoresistance, diagnosis, and prognosis of colorectal cancer

Abstract: Plenty of factors affect the oncogenesis and progression of colorectal cancer in the tumor microenvironment, including various immune cells, stromal cells, cytokines, and other factors. Chemokine is a member of the cytokine superfamily. It is an indispensable component in the tumor microenvironment. Chemokines play an antitumor or pro-tumor role by recruitment or polarization of recruiting immune cells. Meanwhile, chemokines, as signal molecules, participate in the formation of a cross talk among signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 168 publications
(137 reference statements)
0
9
0
Order By: Relevance
“…Functionally, CCL3 promotes cancer growth by stimulating proliferation, migration, and invasion, acting via the TRAF6/NF-κB pathway [27]. Moreover, it recruits cancer-associated fibroblasts (CAFs) and is highly expressed in tumor-associated macrophages (TAMs) [33]. Furthermore, CCL3 has been reported to induce angiogenesis [34] and facilitate osteolytic bone metastases of several cancers [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, CCL3 promotes cancer growth by stimulating proliferation, migration, and invasion, acting via the TRAF6/NF-κB pathway [27]. Moreover, it recruits cancer-associated fibroblasts (CAFs) and is highly expressed in tumor-associated macrophages (TAMs) [33]. Furthermore, CCL3 has been reported to induce angiogenesis [34] and facilitate osteolytic bone metastases of several cancers [35].…”
Section: Discussionmentioning
confidence: 99%
“…CCL4 is also upregulated in CRC [25,30] and its systematic concentrations are elevated [31,32]. The chemokine acts similarly to CCL3 with respect to being a promoter of cancer cell proliferation and survival [33] and a facilitator of metastasis [37,42]. In turn, the anti-tumor effects of CCL4 are associated with recruitment of CD103 + DCs [33], responsible for priming and activating CD8 + T cells recruited into TME [43].…”
Section: Discussionmentioning
confidence: 99%
“…However, treatment of CRC often fails due to acquired chemotherapy resistance, which is one of the main reasons for an individually poor prognosis in CRC patients. Because of this, intensive work has been carried out to identify mechanisms of CRC chemoresistance, including first analyses of the role of miRs in the chemoresistance of CRC cells and on the potential use of these RNAs for CRC treatment [ 76 , 77 , 78 ]. Interestingly, various studies have already shown that the miR examined in our study can re-sensitize tumor cells to certain chemotherapeutic agents, offering one opportunity for future therapeutic strategies based on our present data in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, chemokines can serve as biomarkers and targets for various tumors, including hepatocellular carcinoma [ 10 ], endometrial cancer [ 11 ], and colorectal cancer [ 12 ]. Recent studies highlighted the role of chemokines in the pathological progression of MM (Fig.…”
Section: Main Textmentioning
confidence: 99%